Managing co-morbidity in COPD - Hurst, John (Henry Stewart Talks, 2012)
COPD is associated with multiple systemic co-morbidities including increased cardiovascular risk, osteoporosis, metabolic disturbance, and skeletal muscle dysfunction, The importance of assessing co-morbidity in COPD, The mechanisms of interaction between COPD and co-morbidities, How to manage co-morbidity in a patient with COPD
Archived at 2021/02/25